Lima Barreto e educação: o protagonismo do oprimido - Silva, José Raimundo Gonçalves da (2014)
The main objective of this work is to verify the presence of the oppressed protagonist , within the characteristics posed by Paulo Freire in Lima Barreto literature and the developments that this role can offer as a symbolic act of inserting these oppressed through a restricted to certain social characteristics of characters . The literary aspects that involve the creation and insertion of the oppressed protagonist will mediated by the concept of genetic structuralism , as proposed by Lucien Goldmann literary theory . The study of the historical and cultural context are extremely important to establish the textual structure of homologous relationships with social structure . Through this perspective of the oppressed protagonist , we study the principle of awareness proposed by Paulo Freire , relating it with the characters of Clara dos Anjos . Aspects related to education , symbolically worked by Lima Barreto , will be studies to the concepts of the educator Paulo Freire.